Fatty compounds from the trunk of coffea robusta - Vo Thi Nga; Duong Thi Nhu Y; Dao Thi Anh Ngoc; Mai Uong Song Giang; Dang Thi Kim Ngan (Journal of Technical Education Science, 2020)
Robusta coffee, Coffea robusta is the primary coffee contributing significantly to the coffee processing industry in Vietnam. Up to now, the research on coffee trees has mainly focused on coffee beans and leaves. Their chemical composition has been investigated and revealed the presence of caffeine, trigonelline, alkaloids, chlorogenic acids, lipids, steroids, terpenoids, etc. Coffee trees planted for harvesting seeds are often cut off after the aging period. To improve efficiency of coffee trees, the research on chemical compositions of Robusta coffee trunk is proposed. Five fatty compounds were isolated from the dried powdered-trunks of Coffea robusta (Rubiaceae), including stearic acid (1), hexacosatrienoic acid (2), 2,3-dihydroxypropyl (21Z,24Z) nonacosa-21,24-dienoate (3), stigmasterol (4), and β-sitosterol 3-O-β-D-glucopyranoside (5). Their chemical structures were elucidated by spectroscopic means as well as comparing with data in the literature. To the best of our knowledge, these substances were isolated for the first time from the trunk of Coffea robusta and it is the first time the compounds 2 and 3 were investigated from this genus.